DESIGN AND OPTIMIZATION OF COMPOSITE WING STRUCTURES FOR NEXT-GENERATION UAVS - Qarshiyev, Jasur (Наука и инновация, 2026)
The rapid expansion of unmanned aerial vehicle (UAV) applications in surveillance, environmental monitoring, logistics, and defense has intensified the demand for lightweight, high-strength, and aerodynamically efficient wing structures. Composite materials, particularly fiber-reinforced polymers, have become central to next-generation UAV wing design due to their superior strength-to-weight ratio, fatigue resistance, and tailoring capabilities. This article reviews the principles of composite wing structural design and optimization, focusing on material selection, laminate configuration, structural topology, and computational optimization methods. Emphasis is placed on finite element modeling, aeroelastic considerations, and multi-objective optimization approaches that balance weight, stiffness, strength, and manufacturability. The study synthesizes findings from established aerospace research to highlight current best practices and future trends in composite wing development for UAV platforms.